Emotional support is the only social support associated with the quality of life of people living with HIV - Ni Wayan Sri Rahayuni; Ketut Tuti Parwati Merati; Dewa Nyoman Wirawan (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: The quality of life of people living with HIV is influenced by many factors, one of which is social support. Social support consists of four elements, namely information, instrumental, emotional and appraisal supports. Publication on the association between the quality of life of people living with HIV and the four elements of social support shows inconsistent results. The purpose of this study is to determine the association between the four elements of social support and the quality of life of people living with HIV. Methods: A cross-sectional survey was carried out at the WM Medika Clinic, Kerti Praja Foundation, Denpasar, Bali. Samples were people living with HIV who came to the clinic between July-August 2018 to take antiretroviral (ARV) drugs. The total number of samples was 92 patients selected through the convenience sampling. Data was collected by conducting individual interviews and consisted of respondent characteristics, quality of life, information, instrumental, emotional and appraisal supports. Data were analyzed using logistic regression to determine the association between social support and quality of life of people living with HIV. Results: Emotional support was the only element of social support found to be significantly associated with quality of life of people living with HIV with AOR=4.918 (95%CI: 1.268-19.082). Whereas the other three elements were not found to be related to the quality of life of people living with HIV, these were instrumental support (AOR=0.865; 95%CI: 0.228-3.278); information support (AOR=0.949; 95%CI: 0.248-3.637); and appraisal support (AOR=0.317; 95%CI: 0.095- 1.057). Conclusion: The quality of life of people living with HIV is found to be related to emotional support and is not found to be related to information, instrumental and appraisal supports. Emotional support needs to be addressed in order to further improve the quality of life of people living with HIV.